Textural Characteristics and Depositional Regime of the Shitalakshya River Sediments, Bangladesh - Sohag Ali; Mrinal Kanti Roy; Md. Mahmodul Islam; Zillur Rahman; Faruk Ahmed; Abdul Alim; Md. Yeasin Arafath (Geofluids)
This study analyzes the depositional regime and textural properties of the sediments from the Shitalakshya River in Bangladesh, enabling us to comprehend how these sediments evolved in a river environment. For this investigation, 30 representative samples were taken from the Shitalakshya River, and their textures were analyzed. The cumulative frequency curve is obtained by using semilog graph paper to plot particle size (in phi scale) against cumulative percent. The statistical parameters such as median (Md), mode (Mo), mean (MZ), standard deviation (σi), skewness (SKi), and kurtosis (KG) were calculated using the percentile of phi values (1%, 5%, 16%, 25%, 50%, 75%, 84%, and 95%). The cumulative curves show that the sediments are deposited through the traction population (1.90%), saltation population (75.64%), and suspension population (22.46%). The median value varies between 0.7Ø and 4.85Ø, with an average of 2.738Ø indicating coarse sand to coarse silt. The analyzed samples have unimodal, bimodal, and polymodal distribution, which indicates the sediments are carried by different tributaries and distributaries in the Sitalakshya River system. The range of 1.46Ø–4.05Ø represented by the observed mean value suggests sand with medium to extremely fine grains. Most of the sediments indicate moderate sorting, which is shown by the standard deviation (sorting), which ranges from 0.399Ø to 1.48Ø. The skewness value ranges between −0.01Ø and 0.66Ø, suggesting near symmetrical skewed, while the kurtosis value ranges from 0.54Ø to 1.87Ø, indicating the sediments are 20% leptokurtic, 20% mesokurtic, and 60% platykurtic. According to the CM plot, the Shitalakshya River is mostly deposited in the area between the rolling and suspension fields, indicating a transportation regime of saltation. The scatter plots of skewness versus sorting and graphic mean versus sorting indicate that the sediments fall within the river sand zone. The energy process discriminant functions of the sediments show that they were deposited by a fluvial process.